2016
DOI: 10.1186/s12936-016-1215-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mild medical hypothermia on in vitro growth of Plasmodium falciparum and the activity of anti-malarial drugs

Abstract: BackgroundCerebral malaria remains a medical emergency with high mortality. Hypo-perfusion due to obstructed blood vessels in the brain is thought to play a key role in the pathophysiology of cerebral malaria leading to neurological impairment, long-term neuro-cognitive sequelae and, potentially, death. Due to the rapid reversibility of vascular obstruction caused by sequestered Plasmodium falciparum, it is hypothesized that mild medical hypothermia—a standard intervention for other medical emergencies—may imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…), though conditions exceeding 39 °C strongly inhibited parasite proliferation in the absence of drug (Fig. 2B), as previously reported (Rehman et al, 2016; Chen et al, 1987). Ring-stage survival was not estimated for parasites treated with a 41 °C pulse because this killed nearly all mock-treated cells.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…), though conditions exceeding 39 °C strongly inhibited parasite proliferation in the absence of drug (Fig. 2B), as previously reported (Rehman et al, 2016; Chen et al, 1987). Ring-stage survival was not estimated for parasites treated with a 41 °C pulse because this killed nearly all mock-treated cells.…”
Section: Resultssupporting
confidence: 89%
“…The dependence on environmental temperature of ring-stage susceptibility to artemisinin was examined by transiently exposing pfk13 wild-type 3D7 parasites to a range of temperatures before and during the RSA 4h . Given previous data suggesting hypothermic conditions (32-34 °C) could enhance anti-plasmodial effects of artemisinin in vitro , estimated as EC 50 in a full life-cycle assay (Rehman et al, 2016), we probed a range of low temperatures (17ºC-36 °C) alongside normothermic (37 °C) conditions in parallel. In contrast to these previous results, our data suggest that environmental temperature and ring-stage artemisinin susceptibility in the 3D7 reference parasite line are negatively correlated in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent in vitro trial suggested that P. falciparum growth was inhibited by medical hypothermia. 10 This was in concordance with other in vitro studies, suggesting FIGURE 2. Computed tomography scan of the head showing severe brain edema at presentation with loss of sulci/gyri differentiation (A) and the complete resolution of brain edema after treatment with restoration of normal radiologic brain anatomy (B).…”
Section: Discussionsupporting
confidence: 91%